Helminthofauna of rainbow smelt (Osmerus mordax dentex) at the northern coast of the Okhotsk Sea - V. V. Pospekhov (Известия ТИНРО)
Results of parasitological studies of rainbow smelt Osmerus mordax dentex Steindachner et Kner, 1870 at the northern coast of the Okhotsk Sea are presented. Its helminth fauna includes 21 species: Cestoda — 8, Trematoda — 7, Nematoda — 4, and Acanthocephala — 2. Almost all these species (19) were detected in the Shelikhov Bay, with the highest species diversity among 4 investigated sites in the secondary Perevolochny Bay (14 species). Six species of helminthes from the smelt dwelling in the northern Okhotsk Sea are known as dangerous for human or other mammals: Nybelinia surmenicola, Diphyllobothrium dendriticum, Hysterothylacium aduncum, Anisakis simplex, Pseudoterranova decipiens, and Corynosoma strumosum. The species diversity of helminthes at the northern coast is comparable with the number of species at the coasts of Kamchatka (16 species: Cestoda — 4, Trematoda — 5, Nematoda — 4, Acanthocephala — 3) and Sakhalin (19 species: Cestoda — 5, Trematoda — 8, Nematoda — 3, Acanthocephala — 3); totally 33 species of helminthes are detected in these three areas. The cestodes Diplocotile olrikii, Bothriocephalus spp., trematodes Bucephaloides iskaensis, Podocotyle atomom, and P. reflexa and nematodes Ascorophis pacificus infect rainbow smelt at the northern coast of the Okhotsk Sea only. The most epidemically significant species Anisakis simplex is widely distributed in all three areas.